The Glorification of Academic Imperialism in an African Citadel of Learning: A Textual Analysis of Lekan Are‟s The Challenge of The Barons - Idowu, Adewumi Samuel (International Journal For Research In Educational Studies, 2016)
The Berlin Conference of 1884/85 which culminated in the scramble for and partitioning of African continent into various states by some European nations, brought negative implications to the psyche of Africans. The partitioning was seen as a ploy devised by western countries to seize advantages by using military forces to cow the Africans, thus carrying away their naturally endowed potential to stage indigenous economic development. This paper therefore, takes a critical look at the various ways by which academic excellence was jettisoned, rubbished to romantic academic mediocrity in order to pave the way for sustaining the illegitimate academic emptiness of the Baron tagged as “experts” in a citadel of learning in an African country. The academic wizardry of the protagonist in the text reveals the bold challenge against the Barons in order to remove academic excellence from the shackles of colonialism.